The 5' flanking region and intron1 of the bovine prion protein gene (PRNP) are responsible for negative feedback regulation of the prion protein. - Guangai Xue; Yoko Aida; Takashi Onodera; Akikazu Sakudo (PLoS ONE, 2012)
Transcription factors regulate gene expression by controlling the transcription rate. Some genes can repress their own expression to prevent over production of the corresponding protein, although the mechanism and significance of this negative feedback regulation remains unclear. In the present study, we describe negative feedback regulation of the bovine prion protein (PrP) gene PRNP in Japanese Black cattle. The PrP-expressing plasmid pEF-boPrP and luciferase-expressing plasmids containing the partial promoter fragment of PRNP incorporating naturally occurring single-nucleotide or insertion/deletion polymorphisms were transfected into N2a cells. Transfection of pEF-boPrP induced PrP overexpression and decreased the promoter activity of PRNP in the wild-type haplotype (23-bp Del, 12-bp Del, and -47C). Reporter gene assays further demonstrated that the 12- and 23-bp Ins/Del polymorphisms, which are thought to be associated with Sp1 (Specific protein 1) and RP58 (Repressor Protein with a predicted molecular mass of 58 kDa), in intron1 and the upstream region, respectively, and an additional polymorphism (-47C→A) in the Sp1-binding site responded differently to PrP overexpression. With the -47C SNP, the presence of the Del in either the 23-bp Ins/Del or the 12-bp Ins/Del allele was essential for the negative feedback caused by PrP overexpression. Furthermore, deletion mutants derived from the wild-type haplotype showed that nucleotides -315 to +2526, which include the 5'-flanking region and exon1, were essential for the response. These results indicate that certain negative feedback response elements are located in these sequences, suggesting that regulation by transcription factors such as Sp1 and RP58 may contribute to the negative feedback mechanism of PRNP.